2008
DOI: 10.1007/s00414-008-0282-y
|View full text |Cite
|
Sign up to set email alerts
|

A regression model applied to gender-specific ethanol elimination rates from blood and breath measurements in non-alcoholics

Abstract: As elimination rates for alcohol are suggested to be gender specific, a novel regression model has been applied to estimate these rates for both men and women using experimentally measured data from 81 female and 96 male volunteers described in previous papers. Breath alcohol measurements were done with the Alcotest 7110 Evidential device and were coupled with concomitant sampling of venous blood. Statistical analyses involved use of a mixed linear model for blood alcohol concentration (BAC) and breath alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
1
12
1
1
Order By: Relevance
“…Likewise, after binge drinking for days or weeks before an arrested a drunken driver might have a faster elimination rate of alcohol, such as 25-30 mg/ 100 mL/h. Elimination rates of alcohol from blood are slightly faster in women compared with men (see Table 8) but not to such an extent that warrants the use of gender-specific values in back calculations as suggested elsewhere [206]. By contrast, gender differences in the distribution volume of ethanol needs to be considered when the amount of alcohol absorbed and distributed in the body is calculated from the measured BAC.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Likewise, after binge drinking for days or weeks before an arrested a drunken driver might have a faster elimination rate of alcohol, such as 25-30 mg/ 100 mL/h. Elimination rates of alcohol from blood are slightly faster in women compared with men (see Table 8) but not to such an extent that warrants the use of gender-specific values in back calculations as suggested elsewhere [206]. By contrast, gender differences in the distribution volume of ethanol needs to be considered when the amount of alcohol absorbed and distributed in the body is calculated from the measured BAC.…”
Section: Discussionmentioning
confidence: 96%
“…In women, the minimum and maximum elimination rates were 12 and 27 mg/100 mL/h compared with 10 and 25 mg/100 mL/h in the men. Also reported in the article were rates of alcohol elimination from breath using a quantitative breath-alcohol analyzer to follow the fate of alcohol in the body [206].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that the V d of ethanol derived from analysis of breath alcohol curves in male and female subjects, assuming a 2,100:1 blood‐breath ratio, agreed well with values expected from analysis of blood samples (Cowan Jr., Weathermon, McCutcheon, & Oliver, ). However, more studies are needed in which ADME of ethanol was characterized from BrAC profiles and pharmacokinetic parameters derived and compared with conventional BAC analysis (Dettling, Witte, Skopp, Graw, & Haffner, ).…”
Section: Discussionmentioning
confidence: 99%
“…In women the chronic consumption of even 20 g of alcohol per day is associated with significant morbidity and mortality owing to hepatotoxicity, whereas men are more resistant up to 30 g of alcohol per day. The possible explanations for this sex-dependent difference include a number of factors such as different pharmacokinetics of alcohol [2], elimination rate of alcohol [3], high endogenous oestrogen levels [4], different metabolic enzyme activities [5,6], alcohol distribution volume in the body [7,8] and enhanced sensitivity of liver cells to inflammatory stimuli [4].…”
Section: Introductionmentioning
confidence: 99%